Suno AI sebagai Media Peningkatan Kreativitas Mencipta Lagu anak bagi IGTKI Kabupaten Semarang - Salafiyah, Nafik; Sunarto Sunarto; Bagus Susetyo; Irfanda Rizki Harmono Sejati; Kidung Sukma Asmarani (Universitas Negeri Semarang, 2026)
This community service activity aims to increase the musical creativity of Kindergarten teachers (IGTKI Semarang Regency) through training in creating songs using Suno AI's auxiliary media. The implementation method includes workshops, practical assistance, and evaluation of work. A total of 45 kindergarten teachers participated in the activity and produced seven children's songs with the theme of environment, affection, cleanliness, love of the homeland, manners, and anti-bullying. The results showed a transformation of the teacher's mindset from just a song user to an original song creator with a higher sense of confidence. The use of AI has been proven to facilitate the creative process while opening up space for music art learning innovation. Service products in the form of songs, teaching modules, mass media publications, and song copyrights are real outputs that can be used sustainably. Thus, this activity not only improves teacher competence, but also enriches the treasure of Indonesian children's songs.